KEMAMPUAN MENULIS TEKS PERSUASIF SISWA KELAS VIII SMP NEGERI 1 SAYAN KABUPATEN MELAWI - Dwi Lestari; Syambasril Syambasril; Agus Syahrani (Universitas Tanjungpura, 2020)
AbstractThis study aims to determine the level of students' ability in write persuasive text on the completeness of text structure, grammar, spelling, and effective sentences. The method used in this research is descriptive study. The research used quantitative research. The population in this study were all students of class VIII SMP Negeri 1 Sayan, and the sample of this study was 34 students. The tool of collecting the data in this research is a test. In analyze the data, technique used is quantitative descriptive technique. The results of the data analysis showed that the students' ability to write persuasive texts based on all the aspects studied was in the sufficient category, with a percentage of 67.36%. Therefore, the students' ability to write persuasive texts should be further improved.Key words: Ability, writing, persuasive text.